A fusion strategy for terrestrial water storage anomaly inversion using joint GNSS and GRACE for Southwest China - Yifan Shen; Wanglong Hou; Huizhong Zhu; Yu Gai; Hao Yu; Pengsheng Gao; Shengkun Nie; Wei Zheng; Qiang Wang (Journal of Hydrology: Regional Studies)
Study region: The southwest China covers Yunnan, Guizhou, Sichuan, Guangxi, and Chongqing. The region is influenced by monsoon climate and complex topography, with complex hydrological processes and significant spatial and temporal heterogeneity. Study focus: The Gravity Recovery and Climate Experiment (GRACE) satellite data demonstrate high accuracy; however, their spatial and temporal resolution is low, and there is a window of almost one year. Conversely, the Global Navigation Satellite System (GNSS) satellite data have high spatial and temporal resolution, but their accuracy is low. In this study, a novel Adaptive Weighted Fusion TWSA Inversion Method (AWFTM) is proposed to achieve the complementary advantages of GNSS and GRACE, in order to invert the TWSA results with high accuracy and high spatial and temporal resolution. New hydrological insights for the region: The temporal and spatial evolution characteristics of TWSA in southwest China from 2011 to 2022 were analyzed using AWFTM inversion. The study found that TWSA increased dramatically during 2014–2016, a phenomenon closely related to the strong convective weather and extreme heavy rainfall triggered by the super El Niño event during the same period, which led to significant changes in regional water storage. Further analysis shows that the TWSA and rainfall data from the AWFTM inversion are highly consistent across the provinces in southwest China, with their peaks located in southwest Yunnan Province and southeast Guangxi Province. The results not only validate the spatial reliability of AWFTM, but also provide a powerful dataset that can support disaster prevention, water resource management, and ecological protection in the region.